PREVALENCE OF INDUCED ABORTION AND ASSOCIATED FACTORS AMONG WOMEN OF REPRODUCTIVE AGE IN HARARI REGION, ETHIOPIA - Jamie, Arif Hussen; Abdosh, Mohammed Zekeria (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Abortion is a very common experience in every culture and society. Out of the 210 million pregnancies that occur each year globally, an estimated 46 million (22%) end up in induced abortion, in relation to that, 19 million women experience unsafe abortions annually.Objective: The aim of the study is to determine the prevalence and associated factors of induced abortion among women of reproductive age group in public health facilities from March 25– April 25, 2019, in Harari Region.Methods: A cross sectional study design was conducted. The sample size was 620 abortion cases. Structured questionnaire was used for data collection. Data were entered to Epi-Data version 3.5.3 and analyzed using SPSS version 20. Descriptive statistics, binary and multivariate logistic regression and odds ratio with 95% confidence intervals was used to identify the independent factors of induced abortion cases status. P-value <0.05 was considered as statistically significant association.Result: The mean age of the respondents was 29.5 years, with a standard deviation of 6.5. In this study the magnitude of induced abortion was 42.7%. Age >30, single marital status, occupational status students and commercial sex worker were statistically significant associated with induced abortion (p<0.05).Conclusion: The study revealed a high level of induced abortion. Unwanted pregnancy is high among abortion patients in the study area. Hence, strict counseling about family planning method reminder, and partner involvement in family planning service should be recommended.